Estimation of neutral beam injector power transferred to KSTAR plasmas - Jong-Gu Kwak; J.H. Jeong; S.C. Hong (Nuclear Engineering and Technology)
KSTAR shows the long pulse capability based on superconducting magnet and NBI plays a crucial role in sustaining the plasma via plasma heating and current driving. So, the accurate NBI power measurement transferred to KSTAR plasma is important for the analysis of plasma transport as well as plasma performance parameters. In a long pulse operation, the water coolant temperature is at the steady state condition in longer pulse more than 20s and the coupled neutral beam power to KSTAR plasma during the tokamak experiments is rechecked by using water flow calorimetric method after the experiment. The effect of beam duct scraper loss which was not considered at the neutral beam power calibration process is less than 5 % in terms of neutral beam power. However, in long pulse operation of NBI in KSTAR experiments, high strength of stray PF affects the beam path, the neutral beam power registered on mds + using beam current method is over estimated and it is calculated up to a few percent in terms of neutral beam power using calorimetric method. Therefore, it is necessary to consider the beam power variation by PF effect to interpret the plasma performance degradation in long pulse operation. Lastly. when the ion source tun on or turn off in condition other ion sources are operated, the beam transmission power is also affected because of sharing the beam box for ion sources so that the careful power estimation is necessary for such kind of beam power modulation experiments in KSTAR.